2019
DOI: 10.1002/cam4.2419
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis signatures of the microbial profile in tissue from bladder cancer

Abstract: BackgroundTo examine the microbial profiles in parenchyma tissues in bladder cancer.MethodsTissue samples of cancerous bladder mucosa were collected from patients diagnosed with bladder cancer (22 carcinoma tissues and 12 adjacent normal tissues). The V3‐V4 region of the bacterial 16S rRNA gene was PCR amplified, followed by sequencing on an Illumina MiSeq platform. Bioinformatics analysis for microbial classification and functional assessment was performed to assess bladder microbiome diversity and variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 38 publications
(80 reference statements)
12
92
0
Order By: Relevance
“…Our previous study (Wu et al, 2018) has shown increased bacterial richness, enrichment of some bacterial genera (e.g., Acinetobacter, Anaerococcus, and Sphingobacterium) and decrease of some bacterial genera (e.g., Serratia, Proteus, and Roseomonas) in bladder cancer group when compared with non-cancer group. It is worthy of note that higher abundance of the Acinetobacter in bladder cancer samples was also presented in several other studies (Liu et al, 2019;Mai et al, 2019). Acinetobacter components could play a role in carcinogenesis, by the activation of NF-kB, in animal models of bladder cancer (Roperto et al, 2012).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our previous study (Wu et al, 2018) has shown increased bacterial richness, enrichment of some bacterial genera (e.g., Acinetobacter, Anaerococcus, and Sphingobacterium) and decrease of some bacterial genera (e.g., Serratia, Proteus, and Roseomonas) in bladder cancer group when compared with non-cancer group. It is worthy of note that higher abundance of the Acinetobacter in bladder cancer samples was also presented in several other studies (Liu et al, 2019;Mai et al, 2019). Acinetobacter components could play a role in carcinogenesis, by the activation of NF-kB, in animal models of bladder cancer (Roperto et al, 2012).…”
Section: Introductionsupporting
confidence: 55%
“…It was reported that a higher abundance of Actinomyces was presented in bladder cancer patients, while Bifidobacterium, Streptococcus, Lactobacillus, and Veillonella were enriched in the control group (Bi et al, 2019). Liu et al revealed higher relative abundances of the several microbial genera, such as Acinetobacter and Anoxybacillus, in the cancerous compared to the normal tissues (Liu et al, 2019). Our previous study (Wu et al, 2018) has shown increased bacterial richness, enrichment of some bacterial genera (e.g., Acinetobacter, Anaerococcus, and Sphingobacterium) and decrease of some bacterial genera (e.g., Serratia, Proteus, and Roseomonas) in bladder cancer group when compared with non-cancer group.…”
Section: Introductionmentioning
confidence: 99%
“…Novosphingobium, Ralstonia, Ochrobactrum, Anoxybacillus, and Pseudoxanthomonas were enriched in EC. Previous studies have found Novosphingobium, Anoxybacillus, and Ralstonia are associated with gastric cancer, extrahepatic cholangiocarcinoma and bladder cancer (Avilés-Jiménez et al, 2016;Tseng et al, 2016;Liu et al, 2019a). They play a role in the initiation of inflammation (Rutebemberwa et al, 2014;Tejera et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Vibrio and Cetobacterium are also known as core microbiota of adult zebrafish [ 29 ], which is consistent with our study. L. fermentum HNUB20 inhibited the growth of pathogenic bacteria ( Ochrobactrum ) [ 30 , 31 ], and bacteria associated with disease biomarkers ( Sediminibacterium , Sphingomonas , Sphingobium ) [ 32 34 ]. HNUB20 derived EPS can decrease the level of Pelomonas , which is a biomarker of bladder cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…L. fermentum HNUB20 inhibited the growth of pathogenic bacteria ( Ochrobactrum ) [ 30 , 31 ], and bacteria associated with disease biomarkers ( Sediminibacterium , Sphingomonas , Sphingobium ) [ 32 34 ]. HNUB20 derived EPS can decrease the level of Pelomonas , which is a biomarker of bladder cancer [ 32 ]. It also inhibited the growth of Brachybacterium , which is an end-stage renal disease biomarker ( Brachybacterium ) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%